Large-Scale Agile Frameworks Agile Frameworks, Agile Infrastructure and Pragmatic Solutions for Digital Transformation - Block, Sascha (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2023)
Why should you look at Large-Scale Agile Frameworks? Agility in companies and organizations is becoming increasingly important. This book supports you with practical solutions and tools for the overarching prioritization of requirements for software development. Enable the best possible digital solutions and establish an optimal flow of information in your organization. With agile structures - the Large-Scale Agile Frameworks - organizations become more adaptable. As a result, they can respond faster to change and become more competitive. Science-oriented, Large-Scale Agile Frameworks are examined in the context of Large-Scale Agile Development, agile methodology and tools. With Domain Driven Design, the Scaled Agile Framework (SAFe) and the Spotify Engineering Model, three well-known representatives are presented. Current technology topics such as the cloud trend or the organizational requirements with regard to microservices and IT security are reflected. Content: Agile process models, concepts and basic terms - Software releases and release management - How to adapt and implement a large-scale Agile framework - Cloud trend and virtualization - Software architecture & IT security - Design thinking & Prototyping - Agile Infrastructure and Agile Tools - Software architecture documentation - DevOps methods and tools - ISO / IEC 25010 - Software quality - Data quality Target groups: Project leaders of IT projects, managers, directors, CIOs and CDOs Executives, players and stakeholders in companies and administration digitization Scrum masters, Agile coaches, product owners, IT/software architects The Author: Sascha Block is an IT architect and has several years of practical experience in digitization projects. As a business information scientist with a Master of Science in IT Management and Consulting from the University of Hamburg, the author combines his science-oriented approach with practical experience in agile IT projects to work on innovative and future-oriented solutions in a targeted manner. The translation was done with the help of artificial intelligence. A subsequent human revision was done primarily in terms of content.
Agile process models, concepts and basic terms -- Software releases and release management -- How to adapt and implement a large-scale Agile framework in your organization -- Influencing factors of the cloud trend and virtualization -- Software architecture & IT security as an integral part of agile practice -- Design thinking & prototyping effectively. Using Design Thinking & Prototyping Effectively -- Agile Infrastructure and Agile Tools -- Pragmatic Software Architecture Documentation -- DevOps Methods and DevOps Tools -- ISO/IEC 25010 - Software Quality Criteria -- Data Quality - Lifeblood of Digitalization.
Keywords: Computers, Special purpose; Computer systems; Software engineering; Electronic data processing -- Management; Special Purpose and Application-Based Systems; Computer System Implementation; Software Engineering; IT Operations